Fatal disseminated toxoplasmosis in a feline immunodeficiency virus‐positive cat receiving oclacitinib for feline atopic skin syndrome. Issue 5 (29th May 2022) - Moore, Alexandra; Burrows, Amanda K.; Malik, Richard; Ghubash, Rudayna M.; Last, Robert D.; Remaj, Benjamin
Abstract: Toxoplasma gondii is a ubiquitous protozoan, for which felids are the definitive host. Immunocompromised individuals are susceptible to recrudescent toxoplasmosis. This case describes a 6‐year‐old, feline immunodeficiency virus‐positive domestic short hair cat with feline atopic skin syndrome that developed fatal toxoplasmosis after treatment with oclacitinib for five months. Abstract : Toxoplasma gondii is a ubiquitous protozoan, for which felids are the definitive host. Immunocompromised individuals are susceptible to recrudescent toxoplasmosis. This case describes a 6‐year‐old, feline immunodeficiency virus‐positive domestic short hair cat with feline atopic skin syndrome, that developed fatal toxoplasmosis after treatment with oclacitinib for five months. Résumé: Toxoplasma gondii est un protozoaire ubiquitaire dont les félidés sont l'hôte définitif. Les personnes immunodéprimées sont sensibles à la toxoplasmose recrudescente. Ce cas décrit un chat domestique à poils courts de 6 ans, positif pour le virus de l'immunodéficience féline, atteint du syndrome atopique cutané félin, qui a développé une toxoplasmose mortelle après un traitement à l'oclacitinib pendant cinq mois. Resumen: Toxoplasma gondii es un protozoo ubicuo, cuyo huésped definitivo son los felinos. Las personas inmunocomprometidas son susceptibles a la toxoplasmosis recrudescente. Este caso describe un gato doméstico de pelo corto positivo para el virus de la inmunodeficiencia felina de 6 años de edad con síndrome de piel atópica felina, que desarrolló toxoplasmosis fatal después del tratamiento con oclacitinib durante cinco meses. Zusammenfassung: Toxoplasma gondii ist ein ubiquitäres Protozoon, für welches Felidae den definitiven Wirt darstellen. Immunkompromitierte Individuen sind empfänglich für eine sich verschlimmernde Toxoplasmose. Dieser Fall beschreibt eine 6 Jahre alte Hauskatze, die auf das Feline Immunodefizienz Virus positiv getestet war und am felinen atopischen Hautsyndrom litt, welche nach einer 5 monatigen Behandlung mit Oclacitinib eine fatale Toxoplasmose entwickelte. 要約: Toxoplasma gondii は，ネコ科動物を宿主とする至る所にある原虫である。免疫不全を起こしていると再発性トキソプラズマ症に罹患しやすい。本症例は、猫アトピー性皮膚症候群の猫免疫不全ウイルス陽性ドメスティック・ショート・ヘアー(6歳)が、オクラシチニブによる5カ月間の治療後に致死的なトキソプラズマ症を発症したものである。 摘要: 弓形虫是一种普遍存在的原虫，猫科动物是其终末宿主。免疫功能低下者易患复发性弓形虫病。该病例描述了1只患有猫特应性皮肤综合征的6岁家养短毛猫，猫免疫缺陷病毒阳性，在接受奥拉替尼治疗5个月后发生致死性弓形虫病。 Resumo: Toxoplasma gondii é um protozoário ubíquo para o qual os felídeos são o hospedeiro definitivo. Indivíduos imunocomprometidos são suscetíveis a toxoplasmose recrudescente. Este relato descreve um caso de um felino doméstico de pelo curto de seis anos de idade, positivo para o vírus da imunodeficiência felina, com síndrome atópica felina, que desenvolveu toxoplasmose fatal após tratamento com oclacitinib por cinco meses.